High Entropy Materials Microstructures and Properties - Zhang, Yong (IntechOpen, 2023)
High-Entropy Materials - Microstructures and Properties summarizes recent developments in multicomponent materials. It discusses properties, processing, modeling, and applications of high-entropy materials, including metallic alloys and oxides. It also discusses solidification, sputtering, cryogenic treatments, CALPHAD methodology, biomedical implants, Fe-based superconductors, Fe-rich high-entropy alloys, and more.